SmGRAS1 and SmGRAS2 Regulate the Biosynthesis of Tanshinones and Phenolic Acids in Salvia miltiorrhiza - Li, Wenrui; Bai, Zhenqing; Pei, Tianlin; Yang, Dongfeng; Mao, Renjun; Zhang, Bingxue; Liu, Chuangfeng; Liang, Zongsuo (Frontiers in Plant Science, 2019)
Salvia miltiorrhiza is one of the most widely used traditional Chinese medicinal plants because of its excellent performance in treating heart disease. Tanshinone and phenolic acid are two important metabolites, and their biosynthesis has attracted widespread interest. Here, we functionally characterized SmGRAS1 and SmGRAS2, two GRAS family transcription factors (TFs) from S. miltiorrhiza. SmGRAS1/2 were highly expressed in the root periderm, where tanshinones mainly accumulated in S. miltiorrhiza. Overexpression (OE) of SmGRAS1/2 upregulated tanshinones accumulation and downregulated GA and phenolic acids content and root biomass. However, antisense expression (AE) of SmGRAS1/2 reduced the tanshinones accumulation and increased the GA and phenolic acids contents and root biomass. The expression patterns of biosynthesis genes were consistent with the changes in compounds accumulation. GA treatment increased tanshinones, phenolic acids and GA contents in the OE lines, and restored the root growth inhibited by overexpressing SmGRAS1/2. Subsequently, yeast one-hybrid (Y1H) and electrophoretic mobility shift assays (EMSA) showed SmGRAS1/2 promoted tanshinone biosynthesis by directly binding to the GARE motif in the SmKSL1 promoter in a GA-independent pathway. Taken together, the results revealed that SmGRAS1/2 acted as repressors in GA-mediated root growth and phenolic acid biosynthesis but as positive regulators in tanshinone biosynthesis. Overall, our findings revealed the potential value of SmGRAS1/2 in genetically engineering changes in secondary metabolism.